2016
DOI: 10.1155/2016/5785786
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Stem Cells and Radioresistance: Rho/ROCK Pathway Plea Attention

Abstract: Radiation is the most potent mode of cancer therapy; however, resistance to radiation therapy results in tumor relapse and subsequent fatality. The cancer stem cell (CSC), which has better DNA repair capability, has been shown to contribute to tumor resistance and is an important target for treatment. Signaling molecules such as Notch, Wnt, and DNA repair pathways regulate molecular mechanisms in CSCs; however, none of them have been translated into therapeutic targets. The RhoGTPases and their effector ROCK-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 77 publications
1
20
0
Order By: Relevance
“…IκB is important in this pathway, as it prevents the combination of NF‐κB with DNA . In addition, ROCK proteins, including the two isomers ROCK‐I and ROCK‐II, are members of the serine/threonine protein kinase family and important downstream molecules of Rho . Several studies have shown that ROCK proteins have a close relationship with inflammation .…”
Section: Discussionmentioning
confidence: 99%
“…IκB is important in this pathway, as it prevents the combination of NF‐κB with DNA . In addition, ROCK proteins, including the two isomers ROCK‐I and ROCK‐II, are members of the serine/threonine protein kinase family and important downstream molecules of Rho . Several studies have shown that ROCK proteins have a close relationship with inflammation .…”
Section: Discussionmentioning
confidence: 99%
“…Some of the players found to be affiliated with EMT and cancer stem-like cell maintenance include the PI3K/AKT pathway [ 40 ], RhoA [ 41 ], VEGFR [ 42 ], SOX2 [ 43 ] and Wnt/β-catenin and SHH pathways [ 44 ]. It is not surprising that these pathways present highly attractive targets for therapeutic intervention seeing how they may be involved in the EMT, treatment resistance and plasticity of cancer stem-like cells.…”
Section: Discussionmentioning
confidence: 99%
“…The authors reported that these cells may re-enter the cell cycle 72 h after radio-therapy via a radiation-induced loss of PTEN expression. The loss of PTEN was followed by subsequent activation of the PI3K/Akt pathway, which was reversed using the PI3K/AKT inhibitor perifosine [ 41 ], thereby implicating the PI3K/AKT pathway as a key player in the radio-resistance observed in this model of cancer stem-like cells. This phenomenon highlights the dynamic processes that drive cancer stem-like cell propagation particularly after standard therapeutic applications that may enhance micro-environmental factors within the bulk tumors that drive this plasticity of cancer cells towards an unfavorable, malignant and treatment resistant phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Radioresistance has been implied to be associated with CSCs in multiple types of cancer (31,32). Radiotherapy is the most important method in the treatment of NPC.…”
Section: Discussionmentioning
confidence: 99%